Sedimentary Islands as an Indicator of Surface Water Flows in the Lower Adwan Wadi Basin, South of Al Jabal Al Akhdar (Libya Journal of Geographical Studies, 2025)
This study investigates the sedimentary islands formed in the lower part of the Wadi Adwan basin, located south of the Green Mountain region, with the aim of understanding water flow variations during surface runoff events. The research relied on field observations and morphometric analysis to determine the characteristics of these islands. Fieldwork included measuring the dimensions of the islands, while the descriptive method was used to record their general features, such as their longitudinal or transverse shapes and degree of regularity. The comparative method served as a principal tool for analyzing differences in shape and size among the sedimentary islands. In addition, a quantitative analytical approach was employed to systematically examine the islands, and morphometric techniques were applied using indices such as elongation ratio, form factor, and length-to-width ratio. The findings reveal that sedimentary islands are distributed along the course of the wadi, particularly in flatter sections, and exhibit considerable variation in size, shape, and sediment composition. This reflects the changing intensity and velocity of water flows over time. Their formation is directly linked to periods of reduced flow velocity and sediment accumulation, especially during floods or following repeated dry spells. Water crossing structures also play a significant role in reshaping the islands. Islands north of the culvert were impacted by stronger currents, resulting in elongated shapes and more regular sediment deposition. In contrast, islands south of the culvert formed under weaker currents and are more oval and irregular due to slower sedimentation rates. Long and wide islands, such as Island 6 (19 m in length and 5.5 m in width), may indicate areas of slower flow where greater sediment accumulation occurs. These islands serve as important geomorphological records of hydrological system changes, enabling the tracking of climatic shifts, human activities, and their influence on sediment redistribution within the wadi basin.
Keywords: Sedimentary islands; Wadi Adwan; water flows; lower basin; morphometric analysis